2011
DOI: 10.1118/1.3637493
|View full text |Cite
|
Sign up to set email alerts
|

Paired organs-Should they be treated jointly or separately in internal dosimetry?

Abstract: Left and right counterpart organs always receive different absorbed doses from target organs and deliver different absorbed doses to target organs. Therefore, in application of radiopharmaceuticals in which the dose to the organs plays a role, counterpart organs should be treated separately as two separate organs.© 2011 American Association of Physicists in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 23 publications
(31 reference statements)
0
19
0
Order By: Relevance
“…Several studies have assessed the applicability of the GATE Monte Carlo package for internal dosimetry of radionuclides and related applications [3,4,20,21]. A brief summary of these studies can be found in a published review by Sarrut et al [22].…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have assessed the applicability of the GATE Monte Carlo package for internal dosimetry of radionuclides and related applications [3,4,20,21]. A brief summary of these studies can be found in a published review by Sarrut et al [22].…”
Section: Introductionmentioning
confidence: 98%
“…The SAF values reported by Parach et al . [10] and the maximum relative percentage difference (RD %) for each corresponding pair of organs were also included in the table. The comparison of electron SAFs was limited to five monoenergetic electrons since these energies were considered in the literature[10] to represent the average electron energy of 186 Re, 24 Na, 32 P, 90 Y, and 19 O radionuclides, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On average, electron SAFs calculated by GATE Monte Carlo was also slightly higher values (+0.7%) for self-irradiation and lower values (−4.9%) for cross-irradiation than reported data from the literature. [10]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations